Incorporating the Role(s) of Human Actors in Complex System Design for Safety and Security. Issue 3 (6th October 2021) - Fleming, Elizabeth S.; Williams, Adam D.
ABSTRACT: Traditional systems engineering demonstrates the importance of customer needs in scoping and defining design requirements; yet, in practice, other human stakeholders are often absent from early lifecycle phases. Human factors are often omitted in practice when evaluating and down‐selecting design options due to constraints such as time, money, access to user populations, or difficulty in proving system robustness through the inclusion of human behaviors. Advances in systems engineering increasingly include non‐technical influences into the design, deployment, operations, and maintenance of interacting components to achieve common performance objectives. Such advances highlight the need to better account for the various roles of human actors to achieve desired performance outcomes in complex systems. Many of these efforts seek to infuse lessons and concepts from human factors (enhanced decision‐making through Crew Resource Management), systems safety (Rasmussen's "drift toward danger") and organization science (Giddens' recurrent human acts leading to emergent behaviors) into systems engineering to better understand how socio‐technical interactions impact emergent system performance. Safety and security are examples of complex system performance outcomes that are directly impacted by varying roles of human actors. Using security performance of high consequence facilities as a representative use case, this article will outline the System Context Lenses to understand how to include various roles of human actors into systems engineering design. Several exemplar applications of this organizing lenses will be summarized and used to highlight more generalized insights for the broader systems engineering community.